Relevance of Akerloff’s theory of information asymmetry for the prevention and control of zoonotic infectious diseases in Sub-Saharan Africa: Perspective of Library and Information Services Provision - Ismail Adakawa, Murtala (Advanced Notes in Information Science, 2022)
This paper explores the interconnectedness of library and information services provided as a community strategy for the prevention and control of zoonotic diseases in sub-Saharan Africa. The methodology used in reviewing the literature was a systematic review. In the review, Akerloff’s theory of information asymmetry was used as a lens to guide the study. Within the constructs of the theory, artificial asymmetry was found to be a major factor contributing to the situation where those that are exposed to animals are those that receive little or no information for the prevention of zoonotic diseases and their spread. That is why zoonotic diseases flourish faster among humans. For a long, researchers indicated that domesticating animals in ménage is of psychological and historical linkages that detaching individuals from this practice can present dangers to their lives or threat to their wellbeing. Unfortunately, information penetration to the public about the dangers of domesticating animals is mostly restricted to medical practitioners, epidemiologists, veterinarians, etc. neglecting social sciences, other humanities, and their contributions. This brought many zoonotic diseases literature to be confined within the milieu of healthcare professionals in books, journals, or any other scholarly contents despite calls for interdisciplinary research. This resulted in information asymmetry where the dichotomy between the haves and have-nots continues to widen exponentially, and information received by those interacting closely with animals and the information given by health practitioners is not sufficient to enlighten them proportionally. The study recommended that libraries could play important roles in creating awareness and providing space, relevant information resources, outreach programs, and engaging Civil Society Organizations for crowdfunding, among others for preventing the spread of zoonotic diseases in sub-Saharan Africa.